2003
DOI: 10.3748/wjg.v9.i9.2078
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C/ζ (PRKCZ) Gene is associated with type 2 diabetes in Han population of North China and analysis of its haplotypes

Abstract: PRKCZ gene may be associated with type 2 diabetes in Han population in North China. The haplotypes at five SNP sites in this gene may be responsible for this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The protein kinase C epsilon zeta ( PRKCZ ) is believed to be involved in the translocation of the GLUT4 protein and in the insulin-signalling pathway downstream of PI 3-kinase. Certain SNPs in PRKCZ gene were shown to be associated with T2DM risk in Han Chinese population [ 57 ]. A study was conducted to assess the correlation between T2DM and the DNA methylation of nine CpG sites in the promoter of the PRKCZ gene.…”
Section: Single or Multiple Gene Studiesmentioning
confidence: 99%
“…The protein kinase C epsilon zeta ( PRKCZ ) is believed to be involved in the translocation of the GLUT4 protein and in the insulin-signalling pathway downstream of PI 3-kinase. Certain SNPs in PRKCZ gene were shown to be associated with T2DM risk in Han Chinese population [ 57 ]. A study was conducted to assess the correlation between T2DM and the DNA methylation of nine CpG sites in the promoter of the PRKCZ gene.…”
Section: Single or Multiple Gene Studiesmentioning
confidence: 99%
“…Other genes thought to be associated with type 2 diabetes include the protein kinase C/zeta ( PRKCZ ) gene among Han Chinese in North China (55), the Z +2 allele of the glucokinase gene among Mauritian Creoles (55), and HNF‐1 G319S mutation among Canadian aboriginal youth (56). Other studies have suggested that genes regulating lipid and lipoprotein metabolism may play a role, such as the G‐250A polymorphism of the hepatic lipase gene ( LIPC ) among a Finnish population (57).…”
Section: Factors Associated With the Development Of Type 2 Diabetesmentioning
confidence: 99%
“…Genome-wide association studies have identified a number of gene sequence variants associated with T2D ( 11 , 12 ). Among them, several single nucleotide polymorphisms in the PRKCZ gene have been associated with increased risk of T2D development ( 13 , 14 ). Whether these variants are positively or negatively associated with the activity or expression of the encoded protein is still unknown.…”
Section: Introductionmentioning
confidence: 99%